The vanishing bequest tax: the comparative evolution of bequest taxation in historical perspective - Graziella Bertocchi (Institute for the Study of Labor (IZA), 2007)
Several countries have recently abolished or significantly reduced their taxes on bequests. Bequest taxes, on the other hand, were among the first to be introduced when modern systems of taxation were developed at the end of the nineteenth century. We propose an explanation for these facts which is based on a dynamic political economy model where redistribution is determined not only by wealth inequality but also by sectoral reallocation from agriculture to manufacturing. The model shows that the dynamics of capital accumulation induce a reduction of wealth inequality, which is further accelerated by the redistributive impact of the bequest tax. Through a standard politico-economic mechanism, wealth equalization pushes toward a reduced role of the bequest tax. At the same time, however, a second mechanism is at work, with structural reallocation from agriculture to manufacturing shifting the tax base from hard-to-avoid taxes on land toward easy-to-avoid taxes on capital. The differential treatment of land and capital introduces a source of asymmetry in the tax system which interferes with the determination of the dynamic political equilibrium of the model. Its effect is to compress bequest taxation but also to delay its gradual reduction due to declining wealth inequality. A number of extensions to the basic model allow to match our theory with the long-term evolution of bequest taxation in modern democracies and with the drastic discrepancies currently observed between tax systems in developed and underdeveloped countries.
urn:nbn:de:101:1-20080425167
Keywords: 330; Erbschaftsteuer; Steuerpolitik; Steuerreform; Vermögensverteilung; Strukturwandel; Grundsteuer; Vermögensteuer; Wirtschaftsgeschichte; Theorie